2018
DOI: 10.1021/acs.jafc.8b06136
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Utilization in Lactobacillus fermentum CECT 5716

Abstract: Glutathione, a tripeptide antioxidant, has recently been shown to be either utilized or synthesized by Grampositive bacteria, such as lactic acid bacteria. Glutathione plays an important role in countering environmental stress, such as oxidative stress. In this study, cellular activity regarding glutathione in Lactobacillus fermentum CECT 5716 is characterized. We demonstrate that L. fermentum CECT 5716 has a better survival rate in the presence of glutathione under both oxidative and metal stress. As L. ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…Limosilactobacillus fermentum CECT 5716 (Surya et al, 2018) Streptococcus thermophilus (Qiao et al, 2018) Mutant strain Fructilactobacillus sanfranciscensis DSM20451 gshR lacking the glutathione reductase gene Increase dough rheology; promote the hydrolysis of egg white protein; improve the acid resistance of lactic acid bacteria Latilactobacillus sakei and Fructilactobacillus sanfranciscensis (Loponen et al, 2008) Fructilactobacillus sanfranciscensis (Xu et al, 2018) Ligilactobacillus salivarius (Lee et al, 2010) Enterococcus faecalis, Lactococcus lactis can hydrolyze agmatine into putrescine, NH 3 , CO 2 and ATP through the AgDI pathway, which increases the pH of the cytoplasm (Papadimitriou et al, 2016). In Streptococcus thermophilus, the metabolism of arginine relieves the decrease of intracellular pH by consuming protons and generating NH 3 (Huang et al, 2016).…”
Section: Promotion Of Glutathione Synthesis In Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Limosilactobacillus fermentum CECT 5716 (Surya et al, 2018) Streptococcus thermophilus (Qiao et al, 2018) Mutant strain Fructilactobacillus sanfranciscensis DSM20451 gshR lacking the glutathione reductase gene Increase dough rheology; promote the hydrolysis of egg white protein; improve the acid resistance of lactic acid bacteria Latilactobacillus sakei and Fructilactobacillus sanfranciscensis (Loponen et al, 2008) Fructilactobacillus sanfranciscensis (Xu et al, 2018) Ligilactobacillus salivarius (Lee et al, 2010) Enterococcus faecalis, Lactococcus lactis can hydrolyze agmatine into putrescine, NH 3 , CO 2 and ATP through the AgDI pathway, which increases the pH of the cytoplasm (Papadimitriou et al, 2016). In Streptococcus thermophilus, the metabolism of arginine relieves the decrease of intracellular pH by consuming protons and generating NH 3 (Huang et al, 2016).…”
Section: Promotion Of Glutathione Synthesis In Industrymentioning
confidence: 99%
“…Although Limosilactobacillus fermentum CECT 5716 cannot synthesize glutathione, it can convert oxidized glutathione taken from the environment into reduced glutathione. This also promotes the release of glutathione to the environment ( Surya et al, 2018 ). As an additive, glutathione makes outstanding contributions to increase dough rheology ( Loponen et al, 2008 ) and promote the hydrolysis of egg white protein ( Loponen et al, 2008 ).…”
Section: Products Synthesized By Lactic Acid Bacteriamentioning
confidence: 99%
“…Gor protein protects the cell from oxidative stress with the detoxification of peroxidases using nicotinamide adenine dinucleotide phosphate (NADPH). 69 It would not be surprising to think that the nondetection of Gor could be lethal due to restraining the NADPH recycling for the pentose phosphate pathway, thereby causing problems in energy metabolism. 70 However, it was shown that E. coli with gor mutations could maintain the healthy growth and had enough reduced glutathione.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A strain selected in these early studies, Limosilactobacillus fermentum (formerly Lactobacillus fermentum ) strain ME3 (DSM14241), was reported to improve markers of oxidative stress, such as total antioxidative activity (TAC) or glutathione red/ox ratio in healthy volunteers [ 264 ]. These results prompted later studies with this and other strains of lactobacilli [ 265 ], demonstrating the ability of some of these microorganisms to uptake and reduce the oxidised glutathione from the environment, contributing to the GSH/GSSG balance [ 263 , 266 ]. Moreover, these observations promoted the study of the application of antioxidant lactobacilli in different conditions, with positive results in the reduction of inflammation and myeloperoxidase activity in an animal model of induced colitis [ 267 ] or, more recently, the improvement of vascular endothelial damage in a model of chronic nitric oxide (NO) synthase inhibition [ 268 ].…”
Section: Probiotics As a Therapeutic Tool Against Brain Oxidative Stressmentioning
confidence: 96%
“…Moreover, these observations promoted the study of the application of antioxidant lactobacilli in different conditions, with positive results in the reduction of inflammation and myeloperoxidase activity in an animal model of induced colitis [ 267 ] or, more recently, the improvement of vascular endothelial damage in a model of chronic nitric oxide (NO) synthase inhibition [ 268 ]. Different mechanisms have been proposed for these effects of lactobacilli administration, including the ability to reduce glutathione or to produce enzymes such as feruloyl esterases able to release antioxidant hydroxycinnamic acids from undigested dietary compounds [ 263 , 266 , 269 ]. In addition to the abovementioned mechanisms, the bacterial metabolites, mainly SCFA, may also play a role.…”
Section: Probiotics As a Therapeutic Tool Against Brain Oxidative Stressmentioning
confidence: 99%